Competitive ability of sweet sorghum (Sorghum bicolor (L.) Moench) cultivars against hairy beggarticks (Bidens pilosa L.) - Galon, Leandro; Santin, Carlos Orestes; Radünz, André Luiz; Andres, André; Concenço, Germani; Da Silva, Alexandre Ferreira; Nonemacher, Felipe; Perin, Gismael Francisco; Aspiazú, Ignácio (Revista de Ciencias Agrícolas, 2022)
Among the weeds that interfere with the growth and development of sweet sorghum, beggar ticks stands out, because it has a high competitive capacity for the available resources. This study aims to compare the competitive ability of sweet sorghum (Sorghum bicolor (L.) Moench) against hairy beggarticks (Bidens pilosa L.), as a function of cultivar and plant proportion. Experiments were conducted in a greenhouse in a completely randomized design with four replications and six treatments. Treatments were arranged in replacement series in the proportions of 100:0, 75:25, 50:50, 25:75, and 0:100% (sorghum:weed) equivalent to 20:0, 15:5, 10:10, 5:15 and 0:20 plants per pot with 8 dm3 capacity of sweet sorghum (cultivars ‘BRS 506’, ‘BRS 509’ or ‘BRS 511’) against hairy beggarticks. Fifty days after emergence, plant leaf area (LA), aboveground dry mass (DM), photosynthesis (A), and transpiration rates (E) were measured. Competitive ability was analyzed by using the graphical analysis method and building diagrams based on total and relative productivity. Competitiveness, clustering coefficient, and aggressiveness were also determined. Sorghum cultivars, in general, showed losses independently of the proportion of hairy beggarticks. Statistical analysis showed small differences in competitive ability among sorghum cultivars; ‘BRS 509’ was also demonstrated to be slightly more competitive than ‘BRS 506’ and ‘BRS 511’ against hairy beggarticks. This, however, is unlikely to provide a competitive advantage for ‘BRS 509’ in production fields, and hairy beggarticks should be efficiently controlled early in the crop cycle to avoid productivity losses, independently of the sorghum cultivar.